Great Gilly Hopkins - Paterson, Katherine (New York T.Y. Crowell, 1978)
An eleven-year-old foster child tries to cope with her longings and fears as she schemes against everyone who tries to be friendly.
800L
103511
Keywords: Foster home care; Belonging -- Children Social Psychology; Defense mechanisms (Psychology) in children; Foster children; Families; Accelerated readers